Interventions for sleep problems during pregnancy: A systematic review. (April 2020) - Bacaro, Valeria; Benz, Fee; Pappaccogli, Andrea; De Bartolo, Paola; Johann, Anna F.; Palagini, Laura; Lombardo, Caterina; Feige, Bernd; Riemann, Dieter; Baglioni, Chiara
Summary: Sleep problems during pregnancy are prevalent and could be linked to negative outcomes during pregnancy or post-partum. However, these complaints are often underdiagnosed and undertreated. This review aimed to systematically assess the effectiveness of different interventions to ameliorate poor sleep quality and insomnia during pregnancy. Pubmed, PsycINFO and Medline databases were systematically searched without publication period restriction until 3rd May 2019. Eligible studies had to: include pregnant women of any age and gestational age; use clinical intervention designs targeted at improving sleep outcome; report pre- and post-treatment data for one or more sleep-related outcomes; be published in English, Italian, German, Spanish, or French. Sixteen studies were selected including 1252 expecting mothers. Studies evaluated the efficacy of various interventions: cognitive behavioral interventions for insomnia (4); pharmacotherapy (1); acupuncture (1); mindfulness and yoga (3); relaxation (5) and herbal medication (2). Only six were randomized controlled trials, and only four evaluated longitudinal outcomes. Preliminary support was found for all interventions, but our knowledge is still too limited by lack of evidence. There is an utmost urgency to perform high-quality randomized controlled trials for insomnia interventions during pregnancy and to implement effective programs in standard gynecological care.